Effects of dietary omega-3 fatty acids on growth performance of goat under tropical conditions - Abdelmaged, Kamaleldin Abuelfatah Mohamed; Abu Bakar @ Zakaria, Md Zuki; Goh, Yong Meng; Sazili, Awis Qurni (2012)
The objective of this study was to investigate the effects of diets containing different levels of whole linseed (Linum usitatissimum) as a source of n-3 fatty acid on growth performance of goats in different ages (young and yearling). Twenty four young (5 to 6 months old) and 12 yearling (12 to 13 months old) crossbred Boer goats were assigned to one of three isocaloric and isonitrogenous treatment diets differing in the level of whole linseed. The diets, L0 (control), L10 or L20 contained 0%, 10% and 20% (w/w) whole linseed respectively. The final body weight, total gain and gain to feed ratio were significantly higher in group L20. The DMI was significantly lower in L20 group compared to L0. The final body weight, DMI, and ADG were significantly higher in the yearling animals, while G:F ratio was significantly higher in young goats. However, the total gain was not significantly different between the young and yearling goats.